1973
DOI: 10.1143/jjap.12.797
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxygen on the Properties of GaAs Grown by Liquid Phase Epitaxy

Abstract: Epitaxial layers of GaAs are grown from Ga solution. The effects of oxygen in achieving high purity GaAs layers are investigated. From the experimental results of doping with Ga2O3, the growth temperature dependence of carrier concentration and the impurity profile are explained by the temperature dependence of the distribution coefficient of oxygen in GaAs grown by liquid phase epitaxy. The distribution coefficients of oxygen are 6.5×10-4 at 700°C, 1.8×10-4 at 750°C and 5.1×10-5 at 800°C, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Crystallographic studies of various materials have also been reported. Among these are: "Optical Detection of Magnetic Domains in Birefringent Crystals" (288), "Microcrystals as Nucleus Centers on Rhombohedral Surfaces of Cultured Quartz" (247), "Crystallographic Properties of Chalcomycin I" (193), "Twinning of /3-Cyclotetramethylenetetranitrate (HMX) (189), and "The Optical and Crystallographic Properties of m-Nitrobenzoic Acid" (175).…”
Section: Microscopical Methodsmentioning
confidence: 99%
“…Crystallographic studies of various materials have also been reported. Among these are: "Optical Detection of Magnetic Domains in Birefringent Crystals" (288), "Microcrystals as Nucleus Centers on Rhombohedral Surfaces of Cultured Quartz" (247), "Crystallographic Properties of Chalcomycin I" (193), "Twinning of /3-Cyclotetramethylenetetranitrate (HMX) (189), and "The Optical and Crystallographic Properties of m-Nitrobenzoic Acid" (175).…”
Section: Microscopical Methodsmentioning
confidence: 99%
“…In the case of GaAs epilayers grown from Ga solutions, the most common impurities are generally C (shallow acceptor), 0 (deep donor), Si (shallow donor or acceptor) (for example see Soloman, 1968;Hicks and Greene, 1970;Otsubo et al, 1973;Skromme et al, 1982;Shealy and Woodall, 1982), and S (shallow donor) (Greene, 1986).…”
Section: Epilayer Growth Procedurementioning
confidence: 99%
“…The effect of small concentrations of @ or H20 in the ambient gas during LPE growth on the purity of epilayers makes the control of these two impurities during growth runs extremely important (Otsubo et al, 1973;Morkw and Eastman, 1976). …”
Section: Growth Atmospherementioning
confidence: 99%